2021
DOI: 10.48550/arxiv.2101.11150
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global rigidity for ultra-differentiable quasiperiodic cocycles and its spectral applications

Abstract: For quasiperiodic Schrödinger operators with one-frequency analytic potentials, from dynamical systems side, it has been proved that the corresponding quasiperiodic Schrödinger cocycle is either rotations reducible or has positive Lyapunov exponent for all irrational frequency and almost every energy [AFK11]. From spectral theory side, the "Schrödinger conjecture" [AFK11] and the "Last's intersection spectrum conjecture" have been verified [JM12a]. The proofs of above results crucially depend on the analyticit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Our new Lemmas enable us to not only greatly simplify the proofs in [47], but also optimize almost all estimates in [47]. Our construction is optimal since [17] has shown that for the case of s < 2, the Lyapunov exponent is continuous.…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…Our new Lemmas enable us to not only greatly simplify the proofs in [47], but also optimize almost all estimates in [47]. Our construction is optimal since [17] has shown that for the case of s < 2, the Lyapunov exponent is continuous.…”
Section: 2mentioning
confidence: 99%
“…Remark 1.1. Part (1) of Theorem 1.1 was recently proved in [17] (Theorem 6.3 of [17]), we list here for completeness. The main result of the present paper is part (2).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Combining the approximation argument from [24, Sections 2-4] with the method of [9, Lemma 4], one obtains that if 1 ≤ s < 2 and there exists a rational p/q with |α − p/q| < 1/q 2 , then (14) holds with ̺ = (2 − s)/s for Kq s ≤ N ≤ 2Kq s (cf. [11,Proposition 5], where this fact is stated with implicit exponents). To summarise: 9,24]).…”
Section: Irrational Shiftmentioning
confidence: 99%